A leitura em meio eletrônico como fenômeno informativo e literário do século 21: um levantamento de produção e consumo de livros eletrônicos no Amapá - FERNANDES, Daniele da Rocha (UNIFAP – Universidade Federal do Amapá, 2022)
Due to technological advances that happened in the actual society, the surging of electronic books occurred as a new way of understanding and consuming information. Besides that, it reformulated the concept of traditional book and types of readers. The present study aims to show the reality of this new model of reading in the amapaense journalism, besides of contribute to a better understanding about the consuming of electronic books by professionals of the communication’s area from the state of Amapá. Also search stablish which positive and negative aspects of consuming this type of reading, besides to presenting a survey of journalistic electronic books produced by communicators residing in the state of Amapá.